The Constraint Factors for Implementation of Green Construction Concept in Building Development Project in West Sumatra Province - Arman, Utami Dewi; Sari, Afrilda; Leilany, Lili (Universitas Negeri Padang, 2023)
The construction development in West Sumatra province has not applied much green construction concept. This study aims to identify obstacles in implementing green construction in building construction projects and recommend appropriate solutions for local contractors in overcoming obstacles in their implementation. This research is quantitative descriptive research through the use of questionnaire surveys to selected respondents. The results of data analysis with the parameter ranking weighting method, significant obstacle factors were obtained, including; The implementation of green construction needs longer duration; Lack of ideal guidelines and operational standards regarding the implementation of green construction; The increase of project costs in purchase and management of construction materials; Unreadiness in recruiting professionals and project risks in the project closing out due to specific contract forms. Based on the results, it is expected that the government establishes operational guidelines for the implementation of green construction, prepares an adapted budget and schedule for green construction, professional training and appropriate risk mitigation plan related to green construction contracts.